Exploring biometric attendance technology in the Arab academic environment: Insights into faculty loyalty and educational performance in policy initiatives - Al-Shamsi, Ibrahim Rashid; Shannaq, Boumedyen; Adebiaye, Richmond; Owusu, Theophilus (Journal of Infrastructure, Policy and Development, 2024)
This study provides insights for decision-makers contemplating the implementation of Biometric Attendance Technology (BAT) for faculty in educational institutions. We conducted a comprehensive assessment of BAT’s impact on Arab educational systems, focusing on its influence on faculty loyalty and satisfaction, which are integral to enhancing overall organizational performance. Using SMART-PLS, we analyzed data from an electronic questionnaire distributed to 296 participants. Our findings highlight the importance of fostering faculty loyalty and satisfaction through training and education initiatives alongside BAT implementation strategies. Despite these efforts, there was no significant improvement in the relationship between loyalty, satisfaction, and educational system performance (ESP) following the introduction of BAT. Slope analysis indicated no significant correlations between Faculty Member Satisfaction (FMS), Faculty Member Loyalty (FML), and ESP. However, slight improvements in R-square values were observed: FML increased from 0.512 to 0.514, and ESP from 0.433 to 0.438 with the BAT moderator. These results are crucial for guiding informed decisions regarding the integration of modern technologies into educational systems.